Generic along‐strike segmentation of Afar normal faults, East Africa: Implications on fault growth and stress heterogeneity on seismogenic fault planes. (18th February 2015) - Manighetti, I.; Caulet, C.; De Barros, L.; Perrin, C.; Cappa, F.; Gaudemer, Y.
Abstract Understanding how natural faults are segmented along their length can provide useful insights into fault growth processes, stress distribution on fault planes, and earthquake dynamics. We use cumulative displacement profiles to analyze the two largest scales of segmentation of ∼900 normal faults in Afar, East Africa. We build upon a prior study by Manighetti et al. (2009) and develop a new signal processing method aimed at recovering the number, position, displacement, and length of both the major (i.e., longest) and the subordinate, secondary segments within the faults. Regardless of their length, age, geographic location, total displacement, and slip rate, 90% of the faults contain two to five major segments, whereas more than 70% of these major segments are divided into two to four secondary segments. In each hierarchical rank of fault segmentation, most segments have a similar proportional length, whereas the number of segments slightly decreases with fault structural maturity. The along‐strike segmentation of the Afar faults is thus generic at its two largest scales. We summarize published fault segment data on 42 normal, reverse, and strike‐slip faults worldwide, and find a similar number (two to five) of major and secondary segments across the population. We suggest a fault growth scenario that might account for the generic large‐scale segmentation of faults. The observation of a generic segmentation suggests that seismogenic fault planes are punctuated with a deterministic number of large stress concentrations, which are likely to control the initiation, arrest and hence extent and magnitude of earthquake ruptures.